Private guns, public health - Hemenway, David, 1945- ([Ann Arbor, Michigan] : University of Michigan Press, 2017)
"On an average day in the United States, guns are used to kill over ninety people and wound about three hundred more; yet such facts are accepted as a natural consequence of supposedly high American rates of violence. Private Guns, Public Health reveals the advantages of treating gun violence as a consumer safety and public health problem--an approach that emphasizes prevention over punishment and that has successfully reduced the rates of injury and death from infectious disease, car accidents, and tobacco consumption. Hemenway fair-mindedly and authoritatively outlines a policy course that would significantly reduce gun-related injury and death, pointing us toward a solution"--Publisher's description
Guns and american society -- The scope of the gun problem -- The facts about gun ownership -- The public health approach -- What public health means in practice -- The scientific basis of injury control -- The wrong medicine : good guys and bad guys -- Gun-related injury and death -- Gun accidents -- Suicides -- Homicides -- Other gun-related crimes -- Self-defense use of guns -- The myth and reality of deterrence -- How common is self-defense gun use? -- Is more better? -- How effective is self-defense gun use? -- Location -- Guns in the home -- Guns in schools -- Guns in public.
Includes bibliographical references and index.
Description based on print version record.
eBooks on EBSCOhost
Keywords: Gunshot wounds -- United States -- Prevention; Firearms -- Law and legislation -- United States; Gun control -- United States; Medical policy -- United States; Firearms ownership -- United States; Firearms -- legislation & jurisprudence; Armes à feu -- Contrôle -- États-Unis.; Politique sanitaire -- États-Unis.; Armes à feu -- Possession -- États-Unis.; MEDICAL -- Surgery -- General; Firearms -- Law and legislation; Firearms ownership; Gun control; Medical policy; United States